2020
DOI: 10.1002/ccd.28930
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent aortocoronary arteriovenous fistula after CABG: Systematic review of case reports

Abstract: Objective: To summarize published case reports of aortocoronary arteriovenous fistula (ACAVF) after coronary artery bypass grafting surgery (CABG). Background: Inadvertent ACAVF is a rare complication following CABG. However, the incidence continues to rise, and its management details and clinical outcomes have not been well described. Methods: To identify all published cases of ACAVF following CABG, PubMed, EMBASE, and Scopus were searched through November 2019. We defined ACAVF as inadvertent attachment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In addition, coronary artery fistula can also be caused by acquired factors, such as trauma, cardiac surgery, myocardial biopsy, heart transplantation, infective endocarditis, coronary intervention therapy, etc 10–12 . Some studies believe that coronary artery fistula increases with the increase in the frequency of cardiovascular surgery and other treatment procedures 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, coronary artery fistula can also be caused by acquired factors, such as trauma, cardiac surgery, myocardial biopsy, heart transplantation, infective endocarditis, coronary intervention therapy, etc 10–12 . Some studies believe that coronary artery fistula increases with the increase in the frequency of cardiovascular surgery and other treatment procedures 1 .…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, coronary artery fistula can also be caused by acquired factors, such as trauma, cardiac surgery, myocardial biopsy, heart transplantation, infective endocarditis, coronary intervention therapy, etc. [10][11][12] Some studies believe that coronary artery fistula increases with the increase in the frequency of cardiovascular surgery and other treatment procedures. 1 In this study, there was a patient after left atrial ear occlusion, but no coronary artery fistula was found by preoperative coronary angiography, and a rotatory left atrial ear fistula occurred after surgery (Figure 1).…”
Section: The Differences Between Cpafs and Ccfmentioning
confidence: 99%
“…It brings huge obstacles to the work and spirit of patients, as well as huge economic burden and labor loss to families and society [10]. Therefore, how to effectively promote the recovery of lung function of patients is also the focus of clinical intervention [11,12]. By analyzing the factors affecting pulmonary infection in patients undergoing CABG and proposing nursing measures and invasive examination methods, the occurrence of pulmonary infection can be further reduced.…”
Section: Introductionmentioning
confidence: 99%